Prevalence of dental anxiety and its association with mental health among adults in Kuantan, Malaysia - Mohd, Farah Natashah; Said, Abdul Hadi; Ibrahim, Nurul Ruziantee; Maluin, Nur Afirah; Rahaman, Nabila A. (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: There is a limited number of studies on the prevalence of dental anxiety among the general population in Malaysia and its association with mental health. Purpose: This study aimed to assess the prevalence of dental anxiety and its association with mental health. Methods: This cross-sectional study was conducted among 474 adults attending a public hospital in Kuantan, Malaysia. Participants were required to answer validated, self-administered questionnaires that used the Modified Dental Anxiety Scale (MDAS) and Depression Anxiety and Stress Scale (DASS). Data were analyzed using chi-square and Mann-Whitney tests. Multiple logistic regression was used to determine the relationship between dental anxiety and other variables. Results: A total of 461 respondents completed the questionnaire, with a response rate of 97.3%. The prevalence of dental anxiety among respondents was very high (93.1%). We found that females were 2.3 times more likely to have dental anxiety than males. Meanwhile, an increase in age by one year reduced the likelihood of having dental anxiety by 3%. However, no significant association was found between dental anxiety and mental health. Conclusion: The majority of adults in Kuantan were found to have dental anxiety. Female and younger patients were more likely to have dental anxiety. Our study failed to find any association between dental anxiety and mental health.